2018
DOI: 10.1111/1751-7915.13298
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise modifications of genetic parts reinforce the secretory production of nattokinase in Bacillus subtilis

Abstract: SummaryNattokinase (NK) is an important serine‐protease with direct fibrinolytic activity involving the prevention of cardiovascular disease as an antithrombotic agent. Dozens of studies have focused on the characterization of intrinsic novel promoters and signal peptides to the secretory production of recombinant proteins in Bacillus subtilis. However, intrinsic genetic elements have several drawbacks, which cannot mediate the production of NK to the desired level. In this study, the genetic elements, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…4d). The P BH4 synthetic promoter obtained in this study by SETarSCoP derived from the P srfA is stronger than the previously reported mutants derived from the same parental template by only using a semi-rational design strategy targeting the conserved and non-conservative sequences, upon which the highest yielding level of NK controlled by that evolved promoter was 292 FU/mL at the similar culture condition [65]. Therefore, SETarSCoP is superior to several previous strategies for promoter evolution on different aspects.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…4d). The P BH4 synthetic promoter obtained in this study by SETarSCoP derived from the P srfA is stronger than the previously reported mutants derived from the same parental template by only using a semi-rational design strategy targeting the conserved and non-conservative sequences, upon which the highest yielding level of NK controlled by that evolved promoter was 292 FU/mL at the similar culture condition [65]. Therefore, SETarSCoP is superior to several previous strategies for promoter evolution on different aspects.…”
Section: Resultsmentioning
confidence: 94%
“…The activity of GusA was measured with 4-nitrophenyl β- d -glucuronide (PNPG) as described previously [7]. Strains BSNK and BSBHNK were used to verify the expression level of NK, driven by P srfA and P BH4 and NK activity was determined by a modified fibrin degradation assay [65].…”
Section: Methodsmentioning
confidence: 99%
“…We chose to express the Douchi fibrinolytic enzyme. The enzyme exhibits high thrombolytic activity and it has great application prospects in the prevention and treatment of cardiovascular and cerebrovascular diseases [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that a few posttranslationally dehydrated peptides and a thioetherbridged azurin peptide fragment could be transported via the Sec pathway in L. lactis (30,31). In our initial attempt, five widely used B. subtilis signal peptides, including three Sec signal peptides, SP AmyE (32), SP AprE (33), and SP Epr (34), and two Tat signal peptides, SP PhoD (35) and SP YwbN (36), were each fused to the N terminus of NisA. The fusion peptides were coexpressed with NisB and NisC in B. subtilis WB800.…”
Section: Resultsmentioning
confidence: 99%